Trade-fishing and the dynamics of bream numbering of Dagestan coastline of Caspian Sea and delta water body - L. M. Idrisova (Юг России: экология, развитие)
Comparative analys of the trade-fishing is presented. The leading position of bream in the tradefishing catches of Dagestan and its age staff are shown. The numbering and biomass of bream of Dagestan coastline of Caspian Sea and delta water body are calenlated according to different methods.